PENGEMBANGAN MEDIA PEMBELAJARAN TUTOR PAUD DALAM MENGGALI PERILAKU KERJASAMA ANAK USIA DINI MELALUI GERAK DAN LAGU - Widayati, Tri (JIV-Jurnal Ilmiah Visi, 2009)
Appropriate instructional media facilitates the teacher in improving the quality of teaching-learning process and the students’learning achievment. This research aimed at developing learning media for the tutor of early childhood education to assist him/her to stimulate, develop, and evaluate cooperative behavior of the early age children through movements and songs. The procedures of media development covered need analysis, media development , evaluation and final product in the form of interactive CD. The result of this media development research indicates that the media of interactive CD produced can assist the tutor to stimulate and evaluate the cooperative behavior of early age children through movements and songs. The research findings also give some recommendations for further study.